Demographic and Psychological CEO Traits as Strategic Levers of CSR - Bouzguenda, Mariem; Jarboui, Anis (Journal of Posthumanism, 2025)
This study investigates the determinants of Corporate Social Responsibility (CSR) performance, focusing on how the background and psychological traits of Chief Executive Officers (CEOs) influence a firm’s commitment to CSR. Using data from companies listed on the STOXX Europe 600 index between 2017 and 2023, the analysis explores the impact of six CEO attributes educational background, gender, age, tenure, narcissism, and overconfidence on CSR outcomes through the Feasible Generalized Least Squares (FGLS) method. The results reveal a positive association between CSR performance and several CEO characteristics, including higher education, advanced age, longer tenure, narcissism, and overconfidence. Robustness checks confirm that these effects remain consistent across different CSR dimensions such as resource efficiency, community engagement, and human rights. The findings offer practical insights for corporate boards, suggesting that CEO profiles can serve as strategic levers to enhance CSR performance. By integrating both demographic and psychological CEO traits, this study advances the upper echelons theory and provides a comprehensive perspective linking leadership profiles to the multidimensional nature of CSR.